He ara hou ka tu mai: NZ institutions of higher learning unpacking demands and facilitating change - Hearns, M.; Cockeram, J.; Schott, G.; Bell, T.; Cochrane, T.; Corder, D.; Philpott, A.; Atkins, C.; Diener, S.; Parsons, D.; Falloon, G.; Grimley, M.; et al. (2011)
The Virtual Worlds Working Group began with the DEHub research consortium in November 2009. In December 2010, New Zealand joined the VWWG. This paper highlights the current work of the NZ based members of the group and presents the work of 23 authors at 11 institutes of higher education in New Zealand. The scope of the work covered is diverse, and a number of platforms have been used. Virtual worlds enable educators to provide realistic simulations, engaging role-plays, immersive and genuine tasks, and social interaction that encourages group collaboration, and highlights the ability that virtual worlds have to transform both teaching and learning. © 2011 Merle Hearns, Scott Diener, Michelle Honey, Judy Cockeram, David Parsons, et al.